Cross-cultural validation of the French version of the Lymphedema Functioning, Disability and Health Questionnaire for Upper Limb Lymphedema (Lymph-ICF-UL). Issue 19 (11th September 2021) - De Vrieze, Tessa; Frippiat, Jacqueline; Deltombe, Thierry; Gebruers, Nick; Tjalma, Wiebren A. A.; Nevelsteen, Ines; Thomis, Sarah; Vandermeeren, Liesbeth; Belgrado, Jean-Paul; De Groef, An; Devoogdt, Nele
Abstract: Purpose: Upper limb lymphedema is a vexing morbidity that can occur after the treatment for breast cancer. The Lymphedema Functioning, Disability and Health Questionnaire for Upper Limb Lymphedema (Lymph-ICF-UL) is a valid and reliable tool assessing problems in functioning in patients with breast cancer-related lymphedema. Until now, a French-language version was lacking. The aim of this study was to perform a cross-cultural validation of the French version of the Lymph-ICF-UL questionnaire. Methods: A forward–backward translation process between the original language (Dutch) and the target language (French) was performed. Psychometric properties of this final French version were examined in 50 participants. Results: Intraclass correlation coefficients for test–retest reliability ranged from 0.66 to 0.95. Cronbach's alpha coefficients for internal consistency were higher than 0.77. Face and content validity were very good because the scoring system was clear for all participants (100%), questions were understandable (100%), and all complaints due to BCRL were mentioned by 78% of the participants. Construct validity was moderate. Convergent validity was established since 3 out of 5 expected domains of the Lymph-ICF-UL showed a moderate correlation with expected domains of the 36-item Short-Form Health Survey. There was satisfactory divergent validity as 6 out of 9 hypotheses assessing divergent validity were accepted. Conclusion: The French version of the Lymph-ICF-UL is a reliable and valid questionnaire and ready for use in clinical as well as in scientific practice. Implications for rehabilitation: Since the introduction of more effective treatment modalities increasing the number of breast cancer survivors, the amount of patients dealing with lymphedema is rising likewise up to a pooled incidence rate of more than 16% of the women treated for breast cancer. The French version of the Lymph-ICF-UL is a reliable and valid questionnaire for assessing problems in functioning of patients with breast cancer-related lymphedema of the arm and/or hand. As the questionnaire provides patient information in the different domains of the International Classification of Functioning, Disability and Health, it facilitates evaluating the impact of breast cancer-related lymphedema on daily functioning. Based on the outcomes of the Lymph-ICF-UL treatment goals can be set, where after the questionnaire can be used to monitor long-term results of this treatment and self-care.